Seed traits determine species' responses to fire under varying soil heating scenarios. (23rd July 2020) - Tangney, Ryan; Merritt, David J.; Callow, J. Nikolaus; Fontaine, Joseph B.; Miller, Ben P.
Abstract: Many plant species in fire‐prone environments maintain persistence through fire via soil seedbanks. However, seeds stored within the soil are at risk of mortality from elevated soil temperatures during fire. Seeds may be protected from fire‐temperature impacts by burial, however, those buried too deeply may germinate but fail to emerge. Thus, successful post‐fire seed regeneration is contingent upon a trade‐off between burial depth and survival through fire. We examined the relationships between seedling emergence behaviour, seed survival and soil temperatures during fire in 13 native and four non‐native woodland species in southwestern Australia. We assessed total seedling emergence per depth, maximum seedling emergence depth and seedling emergence speed from seeds planted at eight depths (0, 1, 2, 3, 4, 5, 7, 10 cm). Soil temperatures were quantified using distributed temperature sensing in optic fibre (DTS), measured continuously between 1 and 10 cm in depth (temperatures were subsequently categorized into 1 cm increments for analysis) during five experimental fires in beds with fine fuels manipulated between 8 and 20 t/ha. Using seed survival and emergence success relative to soil temperatures, we determined vulnerability of seedling emergence relative to soil temperatures generated by combustion of fuel quantities typically observed in woodlands. Maximum depth of emergence varied between species from 2 to >10 cm, with a positive linear correlation to seed mass. Maximum soil temperatures from the two highest fuel masses exceeded seed lethal thresholds ( T 50 —representing temperatures lethal to 50% of seeds) of at least five species. Lethal temperatures were exceeded at all potential emergence depths for all three grass species, and all four non‐native species studied. Of the remaining 10 species, temperatures did not exceed the lethal thresholds under any of the fuel mass levels tested. We found no relationship between lethal temperature thresholds and maximum emergence depth. Our data demonstrate that seeds exhibit variation in their response to soil heating and capacity to emerge from depth, with three distinct functional responses amongst our study species, which enable persistence through, and recruitment following, fire. Such variation in species attributes and fuel mass may lead to heterogeneity (within fires) or divergent trajectories (among fires) in community response under changed fire regime. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article